Energy poverty, environmental degradation and agricultural productivity in Sub-Saharan Africa - Stephen Kelechi Dimnwobi; Kingsley Ikechukwu Okere; Favour Chidinma Onuoha; Chukwunonso Ekesiobi (African Governance and Development Institute (AGDI), 2022)
Agricultural productivity remains pivotal to the sustenance of the economies and livelihoods of Sub-Saharan Africa (SSA) countries. Given the emerging threat of energy and environmental uncertainties globally, this study makes a foray into understanding the link among energy poverty, environmental degradation and agricultural productivity in 35 SSA nations in particular, and the nature of their impacts across the sub-region constituents namely; the Central, Eastern, Western and Southern sub-regional blocs in general. To begin, our identified variables comprised of the following: Energy Poverty Index, derived using the principal component analysis, agricultural value added as a share of GDP served as a measure of agricultural productivity and ecological footprint to represent environmental degradation. Subsequently, the instrumental variable generalized method of moment (IV-GMM) technique was implemented for the aggregate SSA model, while the IV-two stage least square technique was adopted for the subregional estimations for the Central, East, West and South African blocs respectively. Major findings from the SSA model revealed that whereas the index of energy poverty has a significant positive influence, ecological footprint exhibited an inverse and significant impact on agricultural productivity, while the Central, East, West and South African models yielded mixed results given regional disparities in economic development, regional variations in agricultural productivity and an imbalance of available resources. Policy recommendations were suggested to, among other things, transform the energy, environmental and agricultural fortunes of the region.
Keywords: 330; Agricultural Productivity; SSA; Energy Poverty; Environmental Degradation; Africa's sub-region